2005
DOI: 10.1007/s11274-004-2613-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and survival of faecal coliforms in activated sludge system in a semi-arid region (Beni Mellal, Morocco)

Abstract: The activated sludge process is one of the biological treatment methods used in many countries to reduce the high levels of organic and mineral pollutants and pathogenic micro-organisms present in wastewater. The present work was undertaken to study the dynamic and antibiotic-resistance of faecal coliforms (FC) in the activated sludge system of Beni Mellal. This work has also as objective the study of the survival of FC, protozoan cysts, helminth eggs and FC antibiotic resistance in the sludge dehydrated in dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 28 publications
0
6
0
3
Order By: Relevance
“…The plates were prepared by adding the antibiotic to molten MullerHinton agar, previously cooled to 458C. Each plate was inoculated with the isolates using the multipoint inoculation method described by Oufdou et al (1999) andFars et al (2005) and incubated at 378C for 24 h. A control plate without antibiotic was prepared and similarly inoculated.…”
Section: Hemolytic Activity and Hemagglutination Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The plates were prepared by adding the antibiotic to molten MullerHinton agar, previously cooled to 458C. Each plate was inoculated with the isolates using the multipoint inoculation method described by Oufdou et al (1999) andFars et al (2005) and incubated at 378C for 24 h. A control plate without antibiotic was prepared and similarly inoculated.…”
Section: Hemolytic Activity and Hemagglutination Assaysmentioning
confidence: 99%
“…These antibiotics were chosen for two reasons: (i) they have been used in the treatment of human and/or livestock illnesses; and (ii) they have been used in previous surveys of antibiotic resistance in aquatic environments (Kelch & Lee 1978;Mezrioui & Oufdou 1996;Oufdou et al 1999;Fars et al 2005).…”
Section: Hemolytic Activity and Hemagglutination Assaysmentioning
confidence: 99%
“…Some researchers have observed little difference in bacterial resistance levels between raw and treated sewage (Espigares et al, 2006;Fars et al, 2005;Fontaine and Hoadley, 1976;Kümmerer et al, 1999;Martins da Costa et al, 2006). Others have concluded that in some instances, antibiotic resistance levels were reduced by the sewage treatment (Bell et al, 1983;Garcia et al, 2007;Guardabassi et al, 2002), contradicting findings that resistance levels can be proportionally elevated in treated effluent depending on the antibiotic, sewage treatment and bacterial genera under investigation (Andersen, 1993;da Silva et al, 2006; Downloaded by [Stony Brook University] at 08:58 20 December 2014 Gallert et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic and antibioticresistant microorganisms in WWTP effluents are a growing public health concern (George et al, 2002;Reinrhaler et al, 2003). Multiple antibiotic resistant fecal coliforms and enterococci including vancomycin resistant Enterococcus (VRE) have been detected in influent, effluent, and sludge from municipal wastewater treatment plants (Blanch et al, 2003;Caplin, et al, 2008;da Costa et al, 2006;Fars et al, 2005;Telabi et al, 2007;Vilanova and Blanch, 2005;Xu et al, 2007). The WWTPs provide a favorable environment for gene transfer because of high bacterial densities and nutritionally rich influent (da Costa et al, 2006;Silva, 2006;Xu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%